2020
DOI: 10.1103/physrevd.101.064038
|View full text |Cite
|
Sign up to set email alerts
|

Power-counting renormalizable, ghost-and-tachyon-free Poincaré gauge theories

Abstract: We present 48 further examples, in addition to the 10 identified in [1], of ghost-and-tachyon-free critical cases of parity-conserving Poincaré gauge theories of gravity (PGT + ) that are also powercounting renormalizable (PCR). This is achieved by extending the range of critical cases considered. Of the new PCR theories, 7 have 2 massless degrees of freedom (d.o.f.) in propagating modes and a massive 0 − or 2 − mode, 8 have only 2 massless d.o.f., and 33 have only massive mode(s). We also clarify the treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…In this section we will extensively revisit Proca and Stueckelberg theories and will follow the analysis with a slightly unorthodox look towards the mechanism of spontaneous symmetry breaking. This subject has been already exposed in [27], but we find necessary to present it here as well, before moving to more complex scenarios. We start analyzing the massive vector system described by the Proca action…”
Section: Proca-stueckelberg-goldstonementioning
confidence: 99%
“…In this section we will extensively revisit Proca and Stueckelberg theories and will follow the analysis with a slightly unorthodox look towards the mechanism of spontaneous symmetry breaking. This subject has been already exposed in [27], but we find necessary to present it here as well, before moving to more complex scenarios. We start analyzing the massive vector system described by the Proca action…”
Section: Proca-stueckelberg-goldstonementioning
confidence: 99%
“…T α µ ν and Q ρµν are linked, respectively, to the geometrical properties of torsion and non-metricity, and aid to easily distinguish different classes of theories when one, or both of them, is set to zero. The resulting model, sometimes in the related form of Poincaré gauge theory, has been lengthily studied [10][11][12][13][14][15][16][17][18][19][20][27][28][29][30][31][32][33]. We relies, in particular, to the form of the 28 parameters MAG action presented in [21], which we reproduce here unadulterated 13)µν c 7 F (13) µν + c 8 F (13) νµ + F (14)µν c 9 F (14) µν + c 10 F (14) νµ + +F (14)µν c 11 F (13) µν + c 12 F (13) νµ + F µν c 13 F µν + c 14 F (13) µν + c 15 F (14) µν…”
Section: The Metric-affine Gravity Actionmentioning
confidence: 99%
“…Indeed, the success of Yang-Mills and Einstein-Hilbert theories appear to indirectly support the relevance of ghost-and tachyon-freedom, as shown in [10,[37][38][39][40]. Considering MAG, extensive literature has been produced to identify sectors of the large parameter space that allow a healthy propagation of additional particles [11][12][13][14][15][16][17][18][19][20][21]. The presence of high-rank fields, carriers of multiple particle states, brings to this search an intrinsic complexity 1 .…”
Section: Introductionmentioning
confidence: 99%
“…unitary theories [4,5]. An exhaustive survey by Lin, Hobson, and Lasenby [6,7] recently found that there are 450 unitary cases in total. Of these, 58 are also power-counting renormalisable (PCR), such that the graviton and roton propagators tend to p −4 and p −2 respectively in the ultraviolet limit 2 .…”
Section: Introductionmentioning
confidence: 99%
“…By implementing the algorithm of Dirac and Bergmann, we are guaranteed to obtain all propagating degrees of freedom (D.o.F), along with all constraints [14]. In the linearised theory, this is especially easy, and allows us to verify the particle spectra and unitarity of the cases obtained in [6,7]. In the nonlinear case, the algorithm allows us to flag potentially fatal pathologies which develop under significant departures from Minkowski spacetime -if this spacetime is taken to be a vacuum, then the nonlinear regime is equivalent to that of strong fields.…”
Section: Introductionmentioning
confidence: 99%